Case 3699: Thorectes Mulsant, 1842 (Insecta, Coleoptera, Scarabaeoidea): proposed conservation of usage - Alonso-Zarazaga, MA; Lobo, JM; López-Colón, JI; Verdú, JR (Bulletin of Zoological Nomenclature, 2015)
The purpose of this application, under Articles 70.3, 74.7 and 81.1 of the Code, is to conserve the current usage of the beetle genus Thorectes Mulsant, 1842 (Insecta, Coleoptera, Scarabaeoidea, Geotrupidae) by confirmation of its type species Scarabaeus laevigatus Fabricius, 1798. This action will also stabilise the predominant usage of another genus, Jekelius López-Colón, 1989, for a phylogenetically relatively distant clade of species whose ecological importance in Mediterranean Quercus forests is currently under study. A lectotype is designated for Scarabaeus laevigatus Fabricius, 1798.
Keywords: Coleoptera; geotrupid beetles; Geotrupidae; Insecta; Nomenclature; Palaearctica; Scarabaeoidea; Scarabaeus laevigatus; taxonomy; Thorectes